Arrival of the gods: revealing the allen landing sites of Nazca - "Von daniken, Erich" (Boston, 1998)
Examines the various theories which attempt to explain the Nazca phenomena in terms of religious ritual, ancient roads, and astrological symbols
Keywords: Comparative religion